2018
DOI: 10.1016/j.jad.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between circulating mitochondrial DNA and inflammatory cytokines in patients with major depression

Abstract: The present findings coincide with our hypothesis that circulating mtDNA contributes to the inflammation in MDD. Further studies are needed to conclude whether plasma mtDNA would be a biomarker of mood disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
75
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 20 publications
8
75
1
Order By: Relevance
“…Conflicting results have been demonstrated regarding correlation between circulating cell‐free mtDNA and IL‐6 in systemic circulation in various diseases . In this study, we found a weak correlation between amniotic fluid supernatant cell‐free mtDNA and IL‐6 levels in fresh uncentrifuged amniotic fluid.…”
Section: Discussioncontrasting
confidence: 78%
“…Conflicting results have been demonstrated regarding correlation between circulating cell‐free mtDNA and IL‐6 in systemic circulation in various diseases . In this study, we found a weak correlation between amniotic fluid supernatant cell‐free mtDNA and IL‐6 levels in fresh uncentrifuged amniotic fluid.…”
Section: Discussioncontrasting
confidence: 78%
“…Immunological markers, including interleukin‐6 and tumor necrosis factor‐α, have been examined, and an elevation of cytokines is a relatively well‐replicated finding …”
Section: Biomarkersmentioning
confidence: 99%
“…194 These indicators are improved by treatment with mood stabilizers. 195 Immunological markers, including interleukin-6 and tumor necrosis factor-α, have been examined, 196 and an elevation of cytokines is a relatively well-replicated finding. 185 In metabolome analysis, elevation of isocitrate in cerebrospinal fluid was reported.…”
Section: Biomarkersmentioning
confidence: 99%
“…Disease is clearly a factor 2-713, 14 , raising the possibility that comorbidities may modulate PD ccf-mtDNA levels. Serum ccf-mtDNA levels are influenced by inflammation [20], BMI [21] and psychosocial and physical stress [22]; factors previously linked to PD progression [23,24]. Elevated plasma ccf-mtDNA levels are associated with nonresponsiveness to selective serotonin reuptake inhibitor (SSRI) treatment in major depressive disorder (MDD) [4] and vitamin C infusion has been shown to reduce plasma ccf-mtDNA levels in sepsis patients [25], suggesting that treatment may be an important cofactor in any ccf-mtDNA assessment.…”
mentioning
confidence: 99%